Synthesis and characterization of star‐shaped PMMA using low‐ppm ARGET ATRP approach and changing to rigid powder for bone cement. Issue 3 (20th June 2021) - Huynh, Mai Duc; Linh, Nguyen Thi Dieu; Huy, Khuc Duong; Chung, Ildoo; Tham, Do Quang
Abstract: Some low‐ppm concentrations of Cu II complex catalyst (15, 30 and 60 ppm) were used for synthesis of 4‐arm star PMMA (4sPMMA) via Atom Transfer Radical Polymerization using Activators Regenerated by Electron Transfer approach (ARGET ATRP). CuBr2 /pentamethyldiethylene triamine and tin(II) 2‐ethylhexanoate were used as a complex catalyst and reducing agent, respectively. Characterization of 4sPMMA samples was performed by using conversion measurement, Fourier transform infrared spectroscopy, nuclear magnetic resonance spectroscopy, gel permeation chromatography (GPC). The obtained results demonstrated that the concentration of Cu II of 30 ppm was suitable to prepare 4sPMMA with high monomer conversion up to 93.9 % at 80 °C for 24 hours (Mn GPC = 29.7 kDa with target Mn of 30 kDa) for our case. Selected product of 4sPMMA in porous powder was next changed to rigid powder. Scanning electron microscopy measurement showed random‐shape morphology of the powder with bead size in the range of 5‐110 μm. Energy dispersive X‐ray analysis indicated that no traces of Cu and Sn metals were detected. The 4sPMMA beads can be prospectively used as a prepolymer component for acrylic bone cement.